Arbitration versus litigation - Lim, Tsu Yee (2014)
The objective of this project is to determine whether arbitration or litigation should be used in resolving commercial disputes. We first defined arbitration and litigation in the Singapore context. Then, we evaluated the merits of arbitration and litigation from a theoretical and practical perspective. We discovered from interviews with some arbitrators that the rosy picture of arbitration painted by the authors of the books and articles we reviewed may not be entirely true. In practice, arbitration can be riddled with problems. We made some recommendations to solve these problems in order to evaluate whether these problems would be so insurmountable that arbitration would be rendered useless in all situations. Our findings reveal that some of these problems could be resolved, consequently we believe that arbitration would be a viable alternative in certain circumstances. To demonstrate arbitration’s usefulness in such circumstances, we used two hypothetical case studies and came up with some proposals.